Liquid and subcritical fluid chromatographic enantioseparation of Nα‐Fmoc proteinogenic amino acids on Quinidine‐based zwitterionic and anion‐exchanger type chiral stationary phases. A comparative study. Issue 6 (19th April 2017) - Lajkó, Gyula; Grecsó, Nóra; Tóth, Gábor; Fülöp, Ferenc; Lindner, Wolfgang; Ilisz, István; Péter, Antal
Abstract: Stereoselective high‐performance liquid chromatographic and subcritical fluid chromatographic separations of 19 N α ‐Fmoc proteinogenic amino acid enantiomers were carried out by using Quinidine ‐based zwitterionic and anion‐exchanger‐type chiral stationary phases Chiralpak ZWIX(−) and QD‐AX. For optimization of retention and enantioselectivity, the ratio of bulk solvent components (MeOH/MeCN, H2 O/MeOH, or CO2 /MeOH) and the nature and concentration of the acid and base additives (counter‐ and co‐ions) were systematically varied. The effect of column temperature on the enantioseparation was investigated and thermodynamic parameters were calculated from the van't Hoff plots ln α vs. 1/T. The thermodynamic parameters revealed that the enantioseparations were enthalpy‐driven. The elution sequence was determined in all cases and with the exception of Fmoc‐Cys(Trt)‐OH, it was identical on both chiral stationary phases whereby the L‐enantiomers eluted before the D‐enantiomers. Abstract :